2018
DOI: 10.1002/jcp.27545
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, cultivation, and characterization of primary bovine cochlear pericytes: A new in vitro model of stria vascularis

Abstract: The study of strial pericytes has gained great interest as they are pivotal for the physiology of stria vascularis. To provide an easily accessible in vitro model, here we described a growth medium‐based approach to obtain and cultivate primary bovine cochlear pericytes (BCP) from the stria vascularis of explanted bovine cochleae. We obtained high‐quality pericytes in 8–10 days with a > 90% purity after the second passage. Immunocytochemical analysis showed a homogeneous population of cells expressing typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(65 reference statements)
1
8
0
Order By: Relevance
“…TNF has been shown to cause cochlear pericytes to contract and thus reduce cochlear blood flow 34 . Additionally, LPS may directly affect cochlear pericytes, as has been observed in different tissues 35 as well as in cochlear pericytes after TNF exposure in vitro 36 …”
Section: Discussion/conclusionmentioning
confidence: 97%
See 1 more Smart Citation
“…TNF has been shown to cause cochlear pericytes to contract and thus reduce cochlear blood flow 34 . Additionally, LPS may directly affect cochlear pericytes, as has been observed in different tissues 35 as well as in cochlear pericytes after TNF exposure in vitro 36 …”
Section: Discussion/conclusionmentioning
confidence: 97%
“…34 Additionally, LPS may directly affect cochlear pericytes, as has been observed in different tissues 35 as well as in cochlear pericytes after TNF exposure in vitro. 36 It has also been shown that in the central nervous system, pericytes are among the first cells to sustain damage in persistent hypoxia 37,38 and-if hypoxia persists long enough-may enter a rigor mortis like state, thus persistently impairing capillary blood flow. 39 Considering the similar physiological properties, a similar mechanism seems well probable.…”
Section: Independent Of How High the Concentration Of Lps Was Appliedmentioning
confidence: 99%
“…Primary human retinal endothelial cells (HRECs) were purchased from Innoprot (Elexalde Derio, Spain) and were fed with culture endothelial cell medium ECM, supplemented with 5% fetal bovine serum (FBS), 1% endothelial cell growth supplement (ECGS), 100 U/mL penicillin, and 100µg/mL streptomycin, provided by Innoprot. HRECs were characterized by their positive immunostaining for von Willebrand factor [ 63 ]. Cells were seeded in flasks or dishes pre-coated with a poly-L-Lysine solution (PLL), at a concentration of 1 mg/mL (Innoprot), for 1 h at 37 °C in a humidified atmosphere of 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…Pericytes with contractile capacity have been identified in several microvascular beds in addition to the retina and brain, where their role in maintaining blood retina/brain barrier and regulating neurovascular coupling at the microcirculatory level have been well-documented [12]. Similarly, cochlear pericytes also express α-SMA [13] and are thought to be involved in regulation of cochlear microcirculation [14, 15]. Renal pericytes as well control medullary blood flow by Ca 2+ -depended contractions [16].…”
Section: Introductionmentioning
confidence: 99%